Enhancing equity, diversity, and inclusion in physics: perspectives from North American underground laboratories - Caden, Erica; Kuula, Samantha; Zens, Rochelle (Frontiers in Physics, 2024)
Equity, Diversity, and Inclusion (EDI) are important to drive innovation in many different fields, including particle physics. Underground labs are working on many different fronts to improve EDI in their host countries and within particle physics collaborations. Laboratories can institute policies to protect their staff and make improvements to their facilities to increase accessibility. Laboratories can encourage the scientific collaborations they host to have policies and plans for increasing EDI. SNOLAB and the Sanford Underground Research Facility (SURF) are each supporting their employees and user-bases in different ways. Some examples are targeted outreach, consultation with experimental collaborations on their own policies, EDI training, and Indigenous cultural recognition. These efforts are intended to enhance the equity and inclusion of their communities.